Attack of the NETs! NETosis primes IL-1β-mediated inflammation in diabetic foot ulcers. Issue 12 (18th June 2020) - Lee, Man K.S.; Sreejit, Gopalkrishna; Nagareddy, Prabhakara R.; Murphy, Andrew J.
Abstract: In volume 133 issue 4 of Clinical Science, Liu et al. showed that neutrophils release extracellular traps (NETs) in the setting of diabetes which acts as a stimulus for NLRP3 inflammasome activation in macrophages to promote IL1β-dependent exacerbation of inflammation. They also provide evidence to show that degrading NETs improves the wound healing process. These findings provide an insight into how NETs communicate with other cells in the vicinity (e.g. macrophages) to exacerbate the inflammatory response. Most importantly, they provide novel avenues to improve wound healing process such as diabetic foot ulcers (DFUs) by targeting NETs.